Cognition and Its Shaping Effect on Sexual Conflict: Integrating Biology and Psychology - Álvarez, Beatriz; Koene, Joris M. (Frontiers in Integrative Neuroscience, 2022)
While genetic variation is of crucial importance for organisms to be able to adapt to their ever-changing environments over generations, cognitive processes can serve the same purpose by acting at shorter time scales. Cognition, and its resulting behaviour, allows animals to display flexible, fast and reversible responses that, without implying a genetic change, are crucial for adaptation and survival. In the research field on sexual conflict, where studies focus on male and female mating strategies that increase the individual’s reproductive fitness while forcing a cost on the partner, the role that cognition may play in how such strategies can be optimised has been widely overlooked. However, a careful analysis of behavioural studies shows that animals can develop and change their responses depending on what they perceive as well as on what they can predict from their experience, which can be of prime importance for optimising their reproductive fitness. As will be reviewed here, largely psychological processes, such as perception, memory, learning and decision-making, can not only modulate sexual conflict, but can also have a big impact on the reproductive success of a given individual. This review highlights the need for a more integrative view of sexual conflict where cognitive processes are also considered as a fundamental part of an animal’s adaptive mating response.